Studi Literatur tentang Pemanfaatan Metode Tetes (Drip Irrigation) pada Tanaman Untuk Mengatasi Kekeringan - Sarah, Ananda; Jahrudin, Ahmad (UNIVERSITAS INDRAPRASTA PGRI, 2023)
In early February 2023, the BMKG predicts that there will be severe drought in June, July and August, even in March 2023 to 2024, the BMKG predicts that the weather in Indonesia will experience an Elnino storm which will cause extreme weather or will feel hotter, it will be very This has an impact on the agricultural sector which really needs water, therefore farmers must have a plan or solution to overcome the water savings that will be needed during the dry season. To overcome the above problems, special methods are needed to save water, therefore researchers will study drip irrigation methods. This research will discuss literature study research regarding drip irrigation. In reviewing literacy studies regarding the use of drip irrigation systems, the author concludes, this application has been widely developed in Indonesia, while the use of the drip method can maximize the efficiency of water use in watering plants, avoid drought during the long dry season, and the most important thing in this irrigation system is regulating the water flow or frequency appropriately so that plants can grow and develop well.